Research on dry port concept as intermodal node - Jaržemskis, Andrius; Vasiliauskas, Aidas V. (Transport, 2007)
The shortage of the free space in the port areas is the reason to search for alternatives. This paper focuses on the dry port concept which is a new approach to solving the mentioned problem. The dry port concept is based on moving of intermodal terminals further to hinterland from the port areas. It helps to avoid traffic bottlenecks, to connect cargo handling from the port with other types of cargo at one common transport centre and it can help develop the hinterland areas. The BSR Interreg III B NP project Inloc (Integrating logistics centre networks in the Baltic Sea Region) showed an initiative to elaborate the concept and to study the feasibility to attract transport operators. The research was done partly by the authors of the article – partners of the Inloc project. Common results of the dry port research and conclusions of the approach elaborated by the article authors are presented. First Published Online: 27 Oct 2010